TINJAUAN YURIDIS PERKAWINAN ADAT SUKU ANAK DALAM DENGAN PERKAWINAN SECARA PERDATA DI KABUPATEN SAROLANGUN JAMBI (Studi Pada Kantor Camat Air Hitam Kab. Sarolangun, Jambi) - William Vincent Purba; Zaini Munawir; Sri Hidayani (Universitas Medan Area, 2022)
The purpose of the study was to find out the legal arrangements in marriage based on customary law and civil law, to determine the impact on the rights of children born in tribal marriages, using data sourced from primary data, secondary data, tertiary data, data collection techniques namely by library research collecting data from books, dictionaries, scientific works, conducting direct interviews with traditional leaders and to the Air Hitam sub-district office, Sarolangun Regency, Jambi. From the results of the research that has been carried out, the authors draw the conclusion that legal arrangements in customary law marriages and civil law are arrangements in marriage based on customary law, marriages carried out on the basis of customary law norms certainly cannot be seen as a violation of rules according to national law because marriage is legal, but on the other hand in this case the government has other rules that must be followed. The impact on the rights of children born in tribal marriages, there will be discriminatory treatment of marriages that are not registered at the Civil Registry Office. The legal consequences, one of which occurs in birth certificates for children whose marriages have not been registered, where the names of the father and mother can be written on the certificate, related to the rights of the child born regarding the division of inheritance in the Tribe of Children. but the absolute right of parents in dividing the share